2013
DOI: 10.1037/a0028648
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the retention and time course of phonotactic constraint learning from production experience.

Abstract: Adults can rapidly learn artificial phonotactic constraints such as /f/ only occurs at the beginning of syllables by producing syllables that contain those constraints. This implicit learning is then reflected in their speech errors. However, second-order constraints in which the placement of a phoneme depends on another characteristic of the syllable (e.g., if the vowel is /æ/, /f/ occurs at the beginning of syllables and /s/ occurs at the end of syllables but if the vowel is /I/, the reverse is true) require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 43 publications
5
61
0
Order By: Relevance
“…The relation between what is learned in the experiment and what had been known before was modeled by Warker and Dell (2006) by first training a connectionist network on English syllables, and then exposing the network to the particular distributions of syllables experienced by participants in the experiments, resulting in further weight changes. Warker (2013) then hypothesized that the changes resulting from experience with the experimental syllables are stored in a separate “mini-grammar” that is associated with the experimental context and hence is immune to interference from everyday English. She supported this proposal by demonstrating that the experimental learning was retained a week later.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relation between what is learned in the experiment and what had been known before was modeled by Warker and Dell (2006) by first training a connectionist network on English syllables, and then exposing the network to the particular distributions of syllables experienced by participants in the experiments, resulting in further weight changes. Warker (2013) then hypothesized that the changes resulting from experience with the experimental syllables are stored in a separate “mini-grammar” that is associated with the experimental context and hence is immune to interference from everyday English. She supported this proposal by demonstrating that the experimental learning was retained a week later.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were all native English speakers, as determined by their responses on a questionnaire at the end of the study that assessed familiarity with English and other languages. Participants were only allowed participation in one of the three experiments, because the learning in these kinds of studies has been shown to persist over long periods of time (Warker, 2013). Nine additional participants were recruited for the experiment but were excluded from analysis because of evidence of non-native English (based upon their answers to the questionnaires), mispronouncing experimentally restricted consonants (for more details, see Stimuli and Procedure below), or technical difficulties resulting in incomplete data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous phonotactic learning experiments (e.g., Chambers, Onishi, & Fisher, 2003, 2010, 2011; Dell, Reed, Adams, & Meyer, 2000; Goldrick & Larson, 2008; Onishi, Chambers, & Fisher, 2002; Seidl, Cristià, Bernard, & Onishi, 2009; Warker, 2013; Warker & Dell, 2006) have described phonotactic patterns at the level of the syllable, but they did not directly test whether representations were at the syllable or word level (since most have used one-syllable, consonant-vowel-consonant or CVC items). The current experiments seek evidence that phonotactic knowledge can be represented at the level of the syllable (or syllable-sized unit), independent of the word, by examining whether syllable-level patterns generalize across word position and word structure, thus asking whether an onset is an onset and a coda is a coda regardless of word structure and position.…”
Section: (3) Evidence Suggesting the Word As A Possible Unit Of Reprementioning
confidence: 99%
“…Phonotactic generalization is used as a tool to better understand how speech sounds are represented, thus measures that assess changes in speech processing as a result of newly-experienced phonotactic patterns allow us to better understand how sound patterns are represented. As the current goal was to assess the influence of constraint violations occurring in different word positions, a continuous recognition memory task was used (e.g., Koo & Callahan, 2012; Mintz, 2002) since production accuracy measures (in which errors on earlier sounds may affect the production of later sounds; e.g., Dell et al, 2000; Goldrick & Larson, 2008; Kittredge & Dell, 2011; Warker, 2013; Warker & Dell, 2006) or repetition latency measures (in which latency is measured from the start of the word; e.g., Chambers et al, 2010; Onishi et al, 2002; Vitevitch & Luce, 2005) may not equally reflect violations at different positions in the word. Moreover, the recognition memory task has advantages over grammaticality judgment tasks (e.g., Vitevitch, Luce, Charles-Luce, & Kemmerer, 1997), in that it is arguably a more implicit measure of phonotactic knowledge.…”
Section: (3) Evidence Suggesting the Word As A Possible Unit Of Reprementioning
confidence: 99%